1994
DOI: 10.3354/meps110187
|View full text |Cite
|
Sign up to set email alerts
|

Population biology of Durvillaea antarctica and Lessonia nigrescens (Phaeophyta) on the rocky shores of southern Chile

Abstract: The Lessonia nigrescens-Durvdlaea antarctica belt is a characteristic feature of the lower intertidal zone along the Chilean coast. This study describes the dynamics of the Lessonja-Durvillaea assemblage in an exposed locality of southern Chile. Abundance, spatial and ten~poral distribution, reproductive penods and response to experimental pruning were quantified. The results revealed differences in population dynamics between species. L. nigrescens had low recruitment, but a longer life expectancy. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 8 publications
2
32
2
Order By: Relevance
“…It is reported that L. nigrescens has high sorption capacity of arsenic from the surrounding aquatic media, as is shown in samples collected in the Valparaiso Bay, Chile ). In the present paper, we observed this absorption capacity in samples collected in the same zone, and at the same time, we can compare this capacity with the lower sorption capacity observed in D. antarctica since both species share their habitat in some zones in the Chilean coast and show competitive interactions (Westermeier et al 1994).…”
Section: Introductionmentioning
confidence: 79%
“…It is reported that L. nigrescens has high sorption capacity of arsenic from the surrounding aquatic media, as is shown in samples collected in the Valparaiso Bay, Chile ). In the present paper, we observed this absorption capacity in samples collected in the same zone, and at the same time, we can compare this capacity with the lower sorption capacity observed in D. antarctica since both species share their habitat in some zones in the Chilean coast and show competitive interactions (Westermeier et al 1994).…”
Section: Introductionmentioning
confidence: 79%
“…The ecological significance of Macrocystis and Lessonia beds along the coast of Chile has been discussed repeatedly by various authors, stressing their role as natural microhabitats, nurseries, protection structures, substrata, and food (Santelices et al 1980;Santelices & Ojeda 1984a;Ojeda & Santelices 1984;Westermeier & Möller 1990;Westermeier et al 1994;Graham et al 2007). Various studies not only evaluated the effects of harvesting techniques, including their immediate impact, but also tried to forecast long-time consequences.…”
Section: Introductionmentioning
confidence: 97%
“…In Bahia Chasco, commercial Macrocystis integrifolia harvesting is based on the thinning of weak adult specimens and the pruning of younger individuals (Westermeier et al 2014a). In contrast, Lessonia berteroana (northern lineage of L. nigrescens; sensu Gonzalez et al 2012) biomass is totally removed from high-energy rocky intertidal areas in the Atacama coast, since pruning schemes have not been successful (Westermeier et al 1994). The age of kelp individuals is frequently ignored, and juvenile specimens are harvested before sexual maturity, with negative consequences.…”
Section: Introductionmentioning
confidence: 97%
“…It is also very abundant along the Chilean coast on exposed rocky shores (Westermeier et al 1994, Fraser et al 2010a. Furthermore, D. antarctica possesses a unique gas-filled honeycomb structure within the blades, which gives strength and extreme buoyancy, and offers protection against potential damage by the strong waves in its natural habitat (Skottsberg 1941, Santelices et al 1980, Hay 1994, Koehl 1999.…”
Section: Introductionmentioning
confidence: 99%